2004
DOI: 10.1143/jjap.43.1269
|View full text |Cite
|
Sign up to set email alerts
|

High Performance Low Temperature Polycrystalline Silicon Thin Film Transistors on Non-alkaline Glass Produced Using Diode Pumped Solid State Continuous Wave Laser Lateral Crystallization

Abstract: High performance low temperature polycrystalline silicon (poly-Si) thin film transistors (TFTs) with large grains were created using diode pumped solid state (DPSS) continuous wave (CW) laser lateral crystallization (CLC), employing fabrication processes at 450°C. Field-effect mobilities of 566 cm2/Vs for the n-channel and 200 cm2/Vs for the p-channel were obtained for a thick Si film (100–150 nm) on a 300×300 mm non-alkaline glass substrate. The high performance of the TFTs is attributed to the predominantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
117
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 124 publications
(121 citation statements)
references
References 21 publications
3
117
1
Order By: Relevance
“…Here, the mobilities are plotted against dielectric thickness, as it is commonly observed that the field effect mobility tends to decrease for thinner dielectrics. The mobility found in our work is in fact very competitive to literature values when regarded in this perspective; higher mobilities are only reported using thicker dielectrics [119,120,152,153].…”
Section: Tft Characterizationcontrasting
confidence: 77%
“…Here, the mobilities are plotted against dielectric thickness, as it is commonly observed that the field effect mobility tends to decrease for thinner dielectrics. The mobility found in our work is in fact very competitive to literature values when regarded in this perspective; higher mobilities are only reported using thicker dielectrics [119,120,152,153].…”
Section: Tft Characterizationcontrasting
confidence: 77%
“…11.14 a and b ) and a hole mobility of ∼ 119 cm 2 /V · s, which is signifi cantly larger than those of organic, amorphous -Si ( < 1 cm 2 /V · s) 65 or conventional p -type poly -Si TFTs ( ∼ 10 -40 cm 2 /V · s), 66 and comparable with that of p -type single -crystal silicon material, such as in a silicon -on -insulator (SOI) MOSFET ( ∼ 180 cm 2 /V · s). 66 Statistical studies also demonstrate that NW -TFTs exhibit highly reproducible and predictable device characteristics, which is critical for practical applications. Figure 11.14 c shows a histogram of the threshold voltage distribution of 20 devices having a standard deviation of only 0.22 V, which can be improved even more by optimizing the device fabrication process.…”
Section: P -Si Nanowire Thin -Film Transistorsmentioning
confidence: 91%
“…64 Electrical transport studies on NW -TFTs assembled from p -type silicon nanowires show characteristics similar to those of conventional enhancement mode p -channel TFTs with an on / off ratio of nearly 8 orders of magnitude (Fig. 11.14 a and b ) and a hole mobility of ∼ 119 cm 2 /V · s, which is signifi cantly larger than those of organic, amorphous -Si ( < 1 cm 2 /V · s) 65 or conventional p -type poly -Si TFTs ( ∼ 10 -40 cm 2 /V · s), 66 and comparable with that of p -type single -crystal silicon material, such as in a silicon -on -insulator (SOI) MOSFET ( ∼ 180 cm 2 /V · s). 66 Statistical studies also demonstrate that NW -TFTs exhibit highly reproducible and predictable device characteristics, which is critical for practical applications.…”
Section: P -Si Nanowire Thin -Film Transistorsmentioning
confidence: 98%
“…These TFTs are called embedded metal double-gate LT poly-Si TFTs (E-MeDG LT polySi TFTs) [50], [51]. The E-MeDG LT poly-Si TFTs comprise lateral grains larger than 2 µm, which are fabricated using diode-pumped solid-state (DPSS) continuous-wave (CW) laser lateral crystallization, which is called the CLC method [52], [53]. The E-MeDG LT poly-Si TFTs exhibited high performance with a nominal mobility greater than 500 cm 2 /Vs and a subthreshold swing (s.s.) of 140 mV/dec.…”
Section: Introductionmentioning
confidence: 99%